Does it hurt? : Depends on who's asking - Modić Stanke, Koraljka (Array, 2019)
The aim of this paper is to determine whether experimenter's professional status (Study 1) and familiarity (Study 2) affect participant's pain assessment, even when there are no other differences in the experimenter's characteristics. Both studies measured pain threshold and tolerance, and assessment of pain unpleasantness and intensity induced by thermal and electrical stimuli. In Study 1, experimenter introduced himself to participants as either a student (lower status) or an expert associate (higher status). ANOVA revealed significant and moderate to large effect of status only in thermal modality; as expected, participants tested by the higher status experimenter displayed higher thermal pain thresholds and tolerances. In Study 2, another experimenter conducted all the measurements; hers (higher) status was previously familiar to one group of students and disclosed to the other group just before the measurement. ANOVA revealed statistically significant and moderate effect of familiarity only in electrical modality; as expected, participants tested by the familiar higher status experimenter displayed higher electrical pain thresholds and tolerances. These results suggest that not only the professional status of a person measuring pain, but also individual's familiarity with it influences someone's pain assessment. With this in mind, researchers are encouraged to conduct studies that control for these factors and to include more information regarding experimenter's characteristics within their reports.